2021
DOI: 10.1002/pchj.490
|View full text |Cite
|
Sign up to set email alerts
|

The effects of written catharsis on anger relief

Abstract: Previous studies have found that "general catharsis", such as hitting sandbags, does not reduce but increases an individual's anger feeling and aggressive behavior. Although the "goal catharsis" that is directed at attacking targets can temporarily relieve anger, there is a risk of increasing the tendency of aggressive personality if it is used for a long time. These findings raise serious doubts and challenges to the traditional view that "anger must be released" held by the classic catharsis theory that many… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Second, we focused on the short-term effects of aggressive fantasizing. Notably, research suggests that these short-term tendencies may translate into long-term outcomes, such as depression or a heightened risk of heart disease (Zhan et al, 2021). Investigating such long-term consequences represents a valuable avenue for future research.…”
Section: Anger Expression-control Hypothesismentioning
confidence: 99%
See 1 more Smart Citation
“…Second, we focused on the short-term effects of aggressive fantasizing. Notably, research suggests that these short-term tendencies may translate into long-term outcomes, such as depression or a heightened risk of heart disease (Zhan et al, 2021). Investigating such long-term consequences represents a valuable avenue for future research.…”
Section: Anger Expression-control Hypothesismentioning
confidence: 99%
“…In the context of psychotherapy, however, some techniques are based on the catharsis hypothesis, proposing that individuals should engage with their anger to promote mental health (Feshbach, 1984; Gentile, 2013). For example, in expressive‐experiential psychotherapy (e.g., expressive writing; Pennebaker, 1997; Zhan et al, 2021), patients are guided to allow themselves to feel and express their emotions (e.g., anger). One notable application of catharsis in psychotherapy, especially with victims of misconduct, involves working with aggressive fantasizing (Haen & Weber, 2009; Seebauer et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Even so, the catharsis or immediate relief alone does not promise a reduction of that behavior or feeling ( Alexander and French, 1946 ; Dollard and Miller, 1950 ; Worchel, 1957 ) and can in many ways exacerbate negative feelings ( Anderson and Bushman, 2002 ; Bushman, 2002 ). Other researchers found that writing down feelings of anger was less effective than writing to the person who made the participant angry, yet neither mode of catharsis alleviated anger responses ( Zhan et al, 2021 ). These findings suggest that whether you were to write to a chatbot and tell it about your anger, or bully it, the behavior would only result in increased aggression toward other people.…”
Section: Part 2: Mechanisms and Types Of Carry-over Effects: Schemas ...mentioning
confidence: 99%